Reevaluating the So-called "Reforms of Urukagina" (2): Their Actual Implementation in the Case of the Maškim Official - Schrakamp, Ingo 1975-; Zólyomi, Gábor (2025)
In his "Reform Texts", Urukagina of Lagash reports that during the time of his predecessors the people of Lagash had suffered from excessive taxes and encroachments by officials, that the ruling family had appropriated the assets of the temple households and claims to have abolished these conditions. While earlier research took Urukagina’s claims at face value, more recent research denied their actual implementation and regarded the "Reform Texts" as mere propaganda. This article discusses the question of the actual implementation of Urukagina’s acts in light of contemporary archival records. Using the example of the maškim official, it demonstrates that the archival records confirm Urukagina’s claim to have removed this official and provides the first proof that a measure was implemented. It thus opens a promising and hitherto neglected venue for future research.
Keywords: ED IIIb / Presargonic Lagash; Reform Texts of Urukagina; archival documents; maškim official; Taxation